GESTIÓN ECONÓMICA EN EL CLARÍN, MEDIO DE COMUNICACIÓN IMPRESA DE LA CIUDAD DE BABAHOYO - Aviles Flores, Nelson Alejandro (2018)
LARIN media printed, was founded in the city of Babahoyo on Tuesday, August 21, 1980 by Mayor Jorge Vaca Mosquera who in turn held the position of administrator of the company, in the beginning EL Clarin was working in a building on June 5 and Barreiro (corner) is now located in its new facilities on November 9 and boardwalk in front of the gerontological center. This work is aimed at analyzing the problems faced by the media Clarin printed in Ecuador due to the lack of revenue from the reduction of advertising space hiring, propagated by public and private companies because of the decrease in the economy, little demand in advertising and insufficient financial income.